Modeling the Effect of Financial Literacy and Inclusion on MSME Sustainability Through Financial Management - Hidayat, Rahmat (ARBITRASE: Journal of Economics and Accounting, 2025)
This study investigates the influence of financial literacy and financial inclusion on the sustainability of micro, small, and medium enterprises (MSMEs) in Mamuju Regency, with financial management as a mediating variable. Data were collected from 112 MSME respondents and analyzed using Partial Least Squares (SmartPLS). The results reveal that financial literacy (? = 0.452, p < 0.001) and financial inclusion (? = 0.417, p < 0.001) both have significant positive effects on sustainability. Moreover, financial management emerged as the most influential factor (? = 0.779, p < 0.001) and significantly mediates the effects of both financial literacy (indirect ? = 0.353, p < 0.001) and financial inclusion (indirect ? = 0.325, p < 0.001) on sustainability. These findings highlight that while knowledge and access are crucial, effective financial management is the key mechanism through which MSMEs can achieve long-term sustainability. The study contributes to the literature by clarifying the mediating role of financial management and offers practical recommendations for strengthening MSME financial practices and policies.